Managing Upper Extremity Clonus With Intramuscular Botulinum Toxin–A Injections in a Patient Poststroke. Issue 5 (31st October 2014) - Kassam, Adam; Phadke, Chetan P.; Ismail, Farooq; Boulias, Chris
Abstract: Spasticity and clonus are common clinical signs of upper motor neuron lesions poststroke. Intramuscular botulinum toxin–A injections have been shown to reduce spasticity and to improve quality of life. Upper extremity clonus can have a significant impact upon activities of daily living and can pose challenges to comfort, self‐care, hygiene, and appearance. Although less common than in the ankle, it is important to understand how upper extremity clonus management may be beneficial to patients presenting with this finding. The majority of previous reports have focused on management of clonus in the lower extremity, but very few have addressed the management of upper extremity clonus. We present a case of poststroke upper extremity clonus with marked improvements following intramuscular botulinum toxin–A injections.